2016
DOI: 10.1055/s-0036-1572538
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life in Patients with Breast Cancer–Related Lymphedema and Reconstructive Breast Surgery

Abstract: Background To evaluate the quality of life (QOL) of breast cancer survivors who have undergone breast reconstruction and have breast cancer-related lymphedema (BCRL). Methods Patients with a unilateral mastectomy with or without breast reconstruction were evaluated for BCRL and their QOL. Patients were divided into a non-BCRL and a BCRL group. Patients with subjective complaints of arm swelling and/or an interlimb volume difference of >200 mL, or undergoing treatment for arm lymphedema were defined as having B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
17
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(23 citation statements)
references
References 23 publications
(30 reference statements)
1
17
0
2
Order By: Relevance
“…53 Presence of lymphedema was identified as a significant predictor of lower physical well-being on the chest, 10 role function, cognitive function, and body image. 2 Five studies out of six (83%) reported that a higher BMI significantly affected the overall quality of life and its physical, psychosocial and sexual dimensions. 31,37,39,52 Regarding smoking status, both studies that identified this variable consistently reported its negative effects on physical, psychosocial, and sexual function.…”
Section: Patients Clinical Characteristicsmentioning
confidence: 99%
“…53 Presence of lymphedema was identified as a significant predictor of lower physical well-being on the chest, 10 role function, cognitive function, and body image. 2 Five studies out of six (83%) reported that a higher BMI significantly affected the overall quality of life and its physical, psychosocial and sexual dimensions. 31,37,39,52 Regarding smoking status, both studies that identified this variable consistently reported its negative effects on physical, psychosocial, and sexual function.…”
Section: Patients Clinical Characteristicsmentioning
confidence: 99%
“…This is in concordance with New Zealand specific data; it was estimated that the incidence of BCRL in New Zealand is 23.3% [ 4 ]. BCRL has a significant impact on breast cancer survivors, including declined physical function and increased disability, which negatively affects quality of life [ 5 8 ]. While the mainstay of BCRL management approaches include compression garments, manual lymphatic drainage, and remedial exercises [ 5 , 9 , 10 ], these interventions are usually time-consuming and poorly adherent (or unacceptable).…”
Section: Introductionmentioning
confidence: 99%
“…(QoL) such as a swollen limb, pain, heaviness, and erysipelas [5][6][7]. Peripheral lymphedema can be classified clinically into severity stages according to the International Society of Lymphology (ISL) [8].…”
mentioning
confidence: 99%
“…Peripheral lymphedema can be classified clinically into severity stages according to the International Society of Lymphology (ISL) [8]. With the increasing breast cancer survival rate and the profound impact on QoL, lymphedema treatment is in high demand [5,6,9,10].…”
mentioning
confidence: 99%